Philosophical problems of science: study aid - Kornienko A. A. Alla Alexandrovna (Tomsk, Tomsk Polytechnic University Publishing House, 2021)
The textbook consists of four sections and aims to promote the understanding of current philosophical views concerning fundamental aspects of the history and methodology of science. The study aid is developed for all master's degree of the TPU.